The Influence of the Principal's Leadership Style and Teachers' Readiness on the Level of Implementation of P5 in Elementary Schools in Paberiwai District - Melkianus Domu Pedi; Riandi Marisa; Sarah Fazilla (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze the influence of principal leadership style and teacher readiness on the implementation level of the Pancasila Student Profile Strengthening Project (P5) in elementary schools throughout Paberiwai District, East Sumba Regency. The study employed a quantitative approach with a survey method. The study population was all elementary school teachers in Paberiwai District, with a sample size of 40 respondents determined through total sampling. Data collection was conducted using a questionnaire that had undergone validity and reliability testing. The data were analyzed using multiple linear regression analysis with the help of SPSS, along with classical assumption tests, t-tests, and F-tests.The results showed that principal leadership style had no significant effect on P5 implementation. Conversely, teacher readiness had a positive and significant partial effect on P5 implementation, with a standardized regression coefficient (β) of 0.441 and a significance level of 0.022 (<0.05), indicating that teacher readiness contributed 19.45% to the variation in P5 implementation. Simultaneously, the principal's leadership style and teacher readiness significantly influenced the implementation of P5, with an R-square value of 0.600. This indicates that the two variables together explain 60.0% of the variation in P5 implementation, while the remainder is influenced by factors outside the research model. Based on these findings, it can be concluded that teacher readiness is a key factor in the successful implementation of P5 in elementary schools throughout Paberiwai District. The role of the principal's leadership style needs to be strengthened to achieve a more tangible impact. This research provides important implications for education management in the 3T (Underdeveloped, 3T) regions, particularly in formulating policies to increase teacher capacity and strengthen school leadership to support the success of the Independent Curriculum through the implementation of P5.